Molecular Dynamics Simulation to Understand the Ability of Anionic Polymers to Alter the Morphology of Calcite - Insil Choi; Il Won Kim (International Journal of Polymer Science)
Molecular dynamics was utilized to investigate the ability of anionic macromolecules to drastically change the morphology of calcite in the presence of magnesium ions. Anionic poly(acrylic acid) and poly(methacrylic acid) were compared with cationic poly(ethylene imine) in their binding behavior on calcite (104) and (110) surfaces. Poly(acrylic acid) and poly(methacrylic acid) showed preferential binding on (110) with strong electrostatic attractions, whereas poly(ethylene imine) was only weakly attracted to (104). The extent of the charge imbalance on the surfaces appeared responsible for the current results, which originated from the deficient number of the coordinating oxygen atoms of carbonate around the surface calcium. The results of the current study were in accordance with the previous experimental observations, where the {hk0} surfaces of calcite were elongated under the coexistence of the anionic polymers and magnesium ions. These results could be generally utilized in the polymer-controlled crystallization with broad implications in the specific interactions with crystal surfaces.